Reactivity of the Bicyclic Amido‐Substituted Silicon(I) Ring Compound Si4{N(SiMe3)Mes}4 with FLP‐Type Character. Issue 69 (5th November 2021) - Schwedtmann, Kevin; Quest, Michael; Guddorf, Benedikt J.; Keuter, Jan; Hepp, Alexander; Feldt, Milica; Droste, Jörn; Hansen, Michael Ryan; Lips, Felicitas
Abstract: The bicyclic amido‐substituted silicon(I) ring compound Si4 {N(SiMe3 )Mes}4 2 (Mes=Mesityl=2, 4, 6‐Me3 C6 H2 ) features enhanced zwitterionic character and different reactivity from the analogous compound Si4 {N(SiMe3 )Dipp}4 1 (Dipp=2, 6‐ i Pr2 C6 H3 ) due to the smaller mesityl substituents. In a reaction with the N‐heterocyclic carbene NHC Me 4 (1, 3, 4, 5‐tetramethyl‐imidazol‐2‐ylidene), we observe adduct formation to give Si4 {N(SiMe3 )Mes}4  ⋅ NHC Me 4 (3 ). This adduct reacts further with the Lewis acid BH3 to yield the Lewis acid–base complex Si4 {N(SiMe3 )Mes}4  ⋅ NHC Me 4  ⋅ BH3 (4 ). Coordination of AlBr3 to 2 leads to the adduct 5 . Calculated proton affinities and fluoride ion affinities reveal highly Lewis basic and very weak Lewis acidic character of the low‐valent silicon atoms in 1 and 2 . This is confirmed by protonation of 1 and 2 with Brookharts acid yielding 6 and 7 . Reaction with diphenylacetylene only occurs at 111 °C with 2 in toluene and is accompanied by fragmentation of 2 to afford the silacyclopropene 8 and the trisilanorbornadiene species 9 . Abstract : An amido‐substituted bicyclic silicon(I) ring compound 2 Si4 {N(SiMe3 )Mes}4 with FLP‐type character forms adducts with the carbene NHC Me 4 and with AlBr3 . The NHC adduct (3 ) further coordinates to BH3 . Compound 2 displays a very weak Lewis acidic and a strong Lewis basic site. This is confirmed by reaction with Brookharts acid to yield 7 . With diphenylacetylene at 111 °C, formal fragmentation into a silylene and a trisilacyclopropenylidene occurs. Both are trapped with the alkyne to afford 8 and 9 .